EFFECTIVENESS OF TELEREHABILITATION FOR MUSCULOSKELETAL SPORT INJURIES: A SYSTEMATIC REVIEW AND META ANALYSIS - Bartosz Golis,; Anna Maria Gęsińska,; Krystian Czyżykowski,; Helena Szelka,; Paweł Edyko,; Alicja Babula,; Wiktor Golus,; Katarzyna Andrzejewska,; Zuzanna Przybyła,; Hubert Woźniak, (International Journal of Innovative Technologies in Social Science, 2025)
Background: Musculoskeletal injuries are among the most common causes of physical disability in athletes, often requiring long-term rehabilitation. Advances in digital health technologies have allowed the uptake of telerehabilitation (TR) over in-person therapy. However, TR's effects in sports-related musculoskeletal injuries have been reported variably at a clinical level.Objective: This systematic review and meta-analysis aim to explore the effectiveness of telerehabilitation compared to traditional rehabilitation in improving functional outcomes, pain relief, and satisfaction among patients with musculoskeletal injuries.Methods: A systematic search of PubMed and related databases revealed 25 peer-reviewed studies published during the period of 2017 to 2025. Eligible studies comprised randomized controlled trials, systematic reviews, and meta-analyses evaluating TR interventions in sport-associated musculoskeletal disorders. Outcomes of interest included pain severity, functional recovery, patient compliance, and patient satisfaction.Results: Most of the studies found that TR led to at least as much or better effects than traditional rehabilitation on pain and functioning outcomes. Meta-analytic search suggested that TR did not differ significantly from face-to-face interventions in the incidence of adverse events. Program duration, adherence rates, and technological access were, however, highlighted as key moderators of efficacy.Conclusions: Telerehabilitation is a safe and effective solution to common musculoskeletal sports injury rehabilitation. Utilization of such a strategy will be limited by adherence to prescribed protocols, patient education, and usage of digital health in order to enhance clinical outcomes and engagement.